Pengaruh Literasi Keuangan, Sikap Keuangan dan Kepribadian terhadap Perilaku Pengelolaan Keuangan pada Pelaku UMKM Kuliner di Shelter Manahan Surakarta - Putri Angelina Silitonga; Dorothea Ririn Indriastuti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the significant influence of financial literacy, financial attitudes, and personality on financial management behavior in Culinary MSME actors at Shelter Manahan Surakarta. The type of data used in this study is quantitative data in the form of answers from respondents that are changed on the Likert scale. The data source used in this study is primary data. The data collection technique in this study was obtained through the distribution of questionnaires to the entire population of 135 respondents, using a saturated sample technique. The data analysis techniques used in this study are descriptive analysis, research instrument test, classical assumption test, t test, F test, and determination coefficient test (????2). The results of the study based on validity and reliability tests showed that all statements regarding financial literacy, financial attitudes and personality were declared valid because of the p-value of 0.05 and reliable because of the Chronbach's alpha > value of 0.60. The results of the classical assumption test showed that all variables passed the tests of multicollinearity, heterokedasticity, autocorrelation, and normal distribution. The results of multiple linear regression analysis obtained the equation Y = 5.748 + 0.207 + 0.252 - 0.024 + e. The results of the t-test (partial) proved that financial literacy and financial attitudes had a significant effect on financial management behavior, while personality had a insignificant effect on financial management behavior. The F test (model accuracy) test showed that the regression model used in this study was appropriate. The test results ????1????2????3????2 showed that the contribution of the influence of independent variables on dependents was 18.5% and the remaining 81.5% was influenced by other model variables.